EcoPedagogy As An Implementative Instrument Of Hifdz AlBi’ah to Achieve Cultural Sustainability - Irawan, Agus Wahyu; Anisah, Zulfatun (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
The accelerating degradation of global ecosystems highlights an urgent moral and pedagogical challenge for Islamic education to promote environmental awareness grounded in faithbased ethics. This study aims to construct a contextual model of ecopedagogy as an implementative instrument of Hifdz alBi’ah (environmental preservation) to strengthen cultural sustainability in coastal Muslim communities of Tuban, East Java. Employing a qualitative descriptive design within the paradigm of ecoIslamic education, this research utilizes an interpretive phenomenological approach involving pesantren teachers, religious leaders, and community activists. Data were collected through indepth interviews, observations, and document analysis, followed by thematic analysis and triangulation to ensure validity. The findings reveal that the integration of Hifdz alBi’ah into ecopedagogical design operates through three stages: (1) internalization of Islamic environmental ethics, (2) transformation of pedagogical practices, and (3) institutional synergy. These processes generate significant impacts, including the revitalization of ecofriendly cultural traditions, the emergence of new Islamic environmental rituals, and the strengthening of ecological religiosity and social solidarity. The study concludes that ecopedagogy, rooted in Yusuf alQaradawi’s environmental ethics, offers a transformative model linking spirituality, ecological literacy, and cultural resilience. Theoretically, this research contributes to the discourse on Islamic ecopedagogy, while practically it provides a replicable framework for Islamic educational institutions to advance sustainabilitybased cultural development in coastal societies.